Desenvolvimento e avaliação de sistema em fluxo para especiação de mercúrio - Tavares, Greice Iop (2007)
A flow injection (FI) system, which is coupled to an atomic absorption spectrometer, is proposed for organic and inorganic mercury speciation. The FI system consists basically of three three way-solenoid valves, a gas/liquid separator and a gold-gauze column. Hg0 and volatile organic mercury species (mainly methylmercury - MeHgH) are generated by reacting inorganic mercury (as Hg(II)) and organic mercury (mainly MeHg+) species with sodium tetraborohydride in HCl medium. The speciation analysis involves two separated steps. In the first, only the volatile mercury obtained by inorganic mercury (Hg(II)) reduction is transported to the quartz cell of the spectrometer where it is measured. In the second step, all volatile mercury species are conducted to a gold-gauze column where they are trapped. Subsequently, the column is heated for mercury releasing, which is then transported to the quartz cell. In this step the total mercury concentration is measured. The concentrations of organic and inorganic mercury are obtained by subtracting the signal measured in the first step from that measured in the second one. The main parameters that influence the FI system performance and mercury speciation were evaluated. The best conditions found were: NaBH4 0.050 % (m/v), HCl 1.0 mol L-1, carrier gas (Ar) flow rate of 25 mL min-1, mercury releasing from the gold-gauze at 500 oC, sample and NaBH4 solutions flow rate of 10 mL min-1 and 2 mL min-1, respectively. The limits of detection, calculated for 10 mL of sample solution processing, were 9.5 ng L-1 of MeHg and 68 ng L-1 of Hg(II). The relative standard deviation (RSD) was typically 2.5%, whereas the calibration curves of Hg(II) and MeHg were linear in the range of 100 to 5000 ng L-1 and 50 to 2000 ng L-1, respectively. The method was applied for organic and inorganic mercury speciation in mineral and underground water. With the proposed FI system it was possible to perform up to 24 measurements per hour. Recovery of spiked organic and inorganic mercury ranged from 97 to 102%. It was concluded that the proposed FI system coupled to atomic absorption spectrometer is very useful and feasible for speciation of very low organic and inorganic mercury. Simplicity, low reagent and sample consumption and good sample throughput are the main characteristics of the system.